Carbon Dioxide Clearance in Critical Care. Issue 1 (January 2013) - Tiruvoipati, R.; Botha, J. A.; Pilcher, D.; Bailey, M.
Lung protective ventilation limiting tidal volumes and airway pressures were proven to reduce mortality in patients with acute severe respiratory failure. Hypercapnia and hypercapnic acidosis is often noted with lung protective ventilation. While the protective effects of lung protective ventilation are well recognised, the role of hypercapnia and hypercapnic acidosis remains debatable. Some clinicians argue that hypercapnia and hypercapnic acidosis protect the lungs and may be associated with improved outcomes. To the contrary, some clinicians do not tolerate hypercapnic acidosis and use various techniques including extracorporeal carbon dioxide elimination to treat hypercapnia and acidosis. This review aims at defining the effects of hypercapnia and hypercapnic acidosis with a focus on the pros and cons of clearing carbon dioxide and the modalities that may enhance carbon dioxide clearance.